2018
DOI: 10.1177/0363546518812820
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dynamic Balance With Sports-Related Concussion: A Prospective Cohort Study

Abstract: Background: Concussion is one of the most common sports-related injuries, with little understood about the modifiable and non-modifiable risk factors. Researchers have yet to evaluate the association between modifiable sensorimotor function variables and concussive injury. Purpose: Investigate the association between dynamic balance performance, a discrete measure of sensorimotor function, and concussive injuries. Study Design: Prospective Cohort Study Methods: One-hundred and nine elite male Rugby Union playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…The intra-session reliability and inter-session reliability of the data acquisition parameters and sensor mounting location have been previously published. 14,15 Furthermore, recent research has demonstrated the discriminant validity of the inertial sensorbased approach, 13,20 as well as highlighted the capacity of the assessment to capture balance deficits with are associated with an increased risk of concussion in rugby union players. 15 It has previously been reported that investigating the discriminant capabilities of inertial sensor-based variables may be the most appropriate method for validation of these tools.…”
Section: Dynamic Balance Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…The intra-session reliability and inter-session reliability of the data acquisition parameters and sensor mounting location have been previously published. 14,15 Furthermore, recent research has demonstrated the discriminant validity of the inertial sensorbased approach, 13,20 as well as highlighted the capacity of the assessment to capture balance deficits with are associated with an increased risk of concussion in rugby union players. 15 It has previously been reported that investigating the discriminant capabilities of inertial sensor-based variables may be the most appropriate method for validation of these tools.…”
Section: Dynamic Balance Testingmentioning
confidence: 99%
“…14,15 Furthermore, recent research has demonstrated the discriminant validity of the inertial sensorbased approach, 13,20 as well as highlighted the capacity of the assessment to capture balance deficits with are associated with an increased risk of concussion in rugby union players. 15 It has previously been reported that investigating the discriminant capabilities of inertial sensor-based variables may be the most appropriate method for validation of these tools. 21 In line with the YBT guidelines, individuals completed four practice trials followed by three recorded trials in the three defined directions: anterior (ANT), posteromedial (PM), and posterolateral (PL) to eliminate the training effect associated with YBT completion.…”
Section: Dynamic Balance Testingmentioning
confidence: 99%
See 3 more Smart Citations